UMA TRILOGIA SINFÔNICA DE EDINO KRIEGER - Tacuchian, Ricardo (DEBATES - Cadernos do Programa de Pós-Graduação em Música, 2014)
A comparative study of three symphonic Works by the Brazilian contemporary composer Edino Krieger, written in a span of tem years (1965-1975): Ludus Symphonicus, Canticum Naturale and Estro Armonico. The affinity among them, holding avant-garde na tradicional compositional behaviors. A brief analysis of each piece of music.